**Answer:**

as per my point to view you can use a L.C.M so you can get the answer or you can try using a exponent way like 5by 1 as n value is 1 so it may give yoh answer

**Answer:**

g(1) = -65; g(n) = g(n-1) -15

**Step-by-step explanation:**

Using n = 1, 2, 3, we can find the first three terms of the sequence:

g(1) = -50 -15 = -65

g(2) = -50 -15(2) = -80

g(3) = -50 -15(3) = -95

The first term of the arithmetic sequence is -65, so that is g(1). Each next term is 15 less than the one before, so the recursive formula is ...

g(n) = g(n-1) -15

The complete recursive function definition requires both parts:

** g(1) = -65**

** g(n) = g(n-1) -15**

**Answer:**

10.58

**Step-by-step explanation:**